2018
DOI: 10.1177/0958305x18790953
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation, characterization, and engine performance of complementary fuel blends of butanol–biodiesel–diesel from Aleurites moluccanus as potential alternative fuels for CI engines

Abstract: Biodiesel has gained worldwide attention due to its renewable aspects. However, it needs more quality improvement. Recently, butanol has been considered as a favorable alternative fuel or additive over methanol and ethanol in compression ignition (CI) engines. In this regard, the present work deals with the evaluation of butanol–diesel–biodiesel blends as potential alternative fuels. In this work, biodiesel has been produced from Aleurites moluccanus oil followed by blending with Euro-diesel and butanol. Impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…13,42,43 In general, up to 5% FFA may be found in crude vegetable oil, 44 and the high FFA of ASO may be associated with cell damage and the gradual decomposition of organic components, which is also reflected by the color of the aged seeds. The density, viscosity, and HHV of the FSO and ASO from both SE and ME are similar and close to the literature-reported range for kukui oils, 0.92 g cm −3 at 15 °C, 13,14,30 24.89−26.91 mm 2 s −1 at 40 °C, 13,14 and 37.61 MJ/kg, 43 respectively. Figure 4A shows the fatty acid profile (FAP) of the SE kukui oils (data S10 and S11) along with that of kamani, canola, 22 pongamia, 22 soybean, 45 jatropha, 45 and carinata oils.…”
Section: Kukui Oilsupporting
confidence: 86%
See 1 more Smart Citation
“…13,42,43 In general, up to 5% FFA may be found in crude vegetable oil, 44 and the high FFA of ASO may be associated with cell damage and the gradual decomposition of organic components, which is also reflected by the color of the aged seeds. The density, viscosity, and HHV of the FSO and ASO from both SE and ME are similar and close to the literature-reported range for kukui oils, 0.92 g cm −3 at 15 °C, 13,14,30 24.89−26.91 mm 2 s −1 at 40 °C, 13,14 and 37.61 MJ/kg, 43 respectively. Figure 4A shows the fatty acid profile (FAP) of the SE kukui oils (data S10 and S11) along with that of kamani, canola, 22 pongamia, 22 soybean, 45 jatropha, 45 and carinata oils.…”
Section: Kukui Oilsupporting
confidence: 86%
“…Although the kukui seed is marketed as a natural weight-loss supplement, many adverse symptoms were reported, which may be associated with the presence of phorbol esters . Currently, the primary application is oil for the cosmetic industry in Hawaii and biodiesel production in Malaysia and Indonesia. ,− With the high oil content of the seeds, the potentially valuable caffeoyl alcohol monolignols or C-lignin-containing shells, , and the high-grade bioadsorbents derived from the shells, , kukui nuts have the potential to serve as a feedstock for sustainable aviation fuel (SAF) and high-value chemicals. A comprehensive understanding of its fuel characteristics can remove one limitation to the use of kukui nuts for SAF and chemical production .…”
Section: Introductionmentioning
confidence: 99%
“…A review by Rajendran 23 suggests that when biodiesel is used along higher alcohols could be an efficient method to improve the performance and emission characteristics of diesel engines. Atabani et al 24 recommended ternary blends of diesel–biodiesel–butanol instead of binary blend of diesel–biodiesel as the properties such as viscosity and density improved with higher alcohol addition. Also, they found that cold flow properties were also in the acceptable range with ternary blends.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, FT-IR was used to define functional groups and bands by a simple analytical technique which was related with kind of stretching and bending vibrations of substances [26].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir) Methodsmentioning
confidence: 99%